THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND ACADEMIC STRESS AMONG FIRST YEAR STUDENTS AT SYIAH KUALA UNIVERSITY - Marhamah, Fauzah; Hamzah, Hazalizah binti (Psikoislamedia: Jurnal Psikologi, 2016)
The purpose of this study was to examine the relationship between social support and academic stress among first year students at Syiah Kuala University (UNSYIAH). Data was collected through questionnaires. The respondents were first year students at UNSYIAH (n = 364) with ranging age from 16 to 21. Respondents completed the Multi Dimensional Scale of Perceived Social Support (MSPSS) and Student Life Stress Inventory (SLSI). Pearson Correlation Analysis was used to analyze the relationship between social support and academic stress among first year students. The results revealed that the sample reported moderate levels of social support and academic stress. Students with high level of social support, reported low level of academic stress.